(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article investigates the problem of influence of the linguistic and extralinguistic factors upon development of branch vocabulary. The interaction of intra- and extralinguistic aspects in the process of forming and functioning the Ukrainian military vocabulary are determined.